Setting the Stage for Success: Readiness and Connectedness as Antecedents of Learning Continuance Intention in Online Learning - Yingqi Tang; Hungwei Tseng; Yu-Chun Kuo; Hsin-Te Yeh; Jianfang Liu (Online Learning)
Through a hierarchical multiple regression analysis, this study investigated how dimensions of online learning readiness and online connectedness would influence students’ intentions to continue to take online courses. Data from 369 students who took at least one online course at a four-year public university showed that online learning readiness had a stronger relationship with continuance intention than online student connectedness, while online learning readiness had a significant correlation with online student connectedness. Online learning readiness and connectedness are indicators of online learning persistence. Factors such as age, computer/internet self-efficacy, self-directed learning, learner control, and facilitation are all elements that influence students' intention to continue with online learning. Moreover, among the five subscales of readiness, motivation has the strongest connection with continuance intention. In addition, course facilitation was positively and significantly related to the intention to continue participating in courses. The study's implications and directions for future research were also explored.